The Application of Several Organic Fertilizers for Production Increase and Brix Content of Sweet Corn (Zea mays L. Saccharate) - Andi Adya Ramadhan Agussalim; Rafiudin Rafiudin; Amir Yassi (Hasanuddin University, 2022)
The tendency of chemical fertilizers used (inorganic) in food crop cultivation farming by the farmers is caused by their practicality. However, the continuous use of chemical fertilizers can damage the crops and their environment, including sweet corn. Sweet corn (Zea mays L. Saccharate) contains high sugar content because it naturally mutates to a recessive gene that controls sugar conversion to starch in corn endosperm. The purpose of this research were to know the effect of several organic fertilizers on productivity increase as well as Brix content of sweet corn. This research was conducted from June to August 2021 in Waempubbu Village, Amali District, Bone Regency and Laboratory of Food Process, Agriculture Faculty, Hasanuddin University, South Sulawesi. This research used the design of a split plot by using completely randomized design (CRD). The main plot was sweet corn varieties: Talenta (v1) and Bonanza (v2). Meanwhile, the subplot was organic fertilizers which are control (p0), compost (p1), soil ameliorant (p2), compost + soil ameliorant (p3), liquid organic fertilizer/LOF (p4), compost + LOF (p5), soil ameliorant + LOF (p6) and compost + soil ameliorant + LOF (p7). According to the results, the Bonanza variety showed high average productivity, 22.50 tons per hectare. The treatment of organic fertilizer that reveals the high average productivity is combines compost + soil ameliorant + LOF (p7). The interaction of treatment that reveals the highest productivity is an interaction between Bonanza variety with the treatment of soil ameliorant + LOF (p6), which is 27.07 tons per hectare with Relative Agronomic Effectiveness (RAE) value is 1366.67%. The treatment of compost fertilizer + soil ameliorant + LOF (p7) exhibits the content of Brix (10.50%) and becomes the highest productivity.